Climate Affects Plant-Soil Feedback of Native and Invasive Grasses: Negative Feedbacks in Stable but Not in Variable Environments - Duell, Eric B.; Zaiger, Katherine; Bever, James D.; Wilson, Gail W. T. (Frontiers in Ecology and Evolution, 2019)
The plant-soil feedback framework allows researchers to target the interaction of plants and root-associated microbes and to determine its interplay on plant-plant interactions. Plant-soil feedbacks in terrestrial ecology are well documented, but the strength and direction of feedbacks as influenced by abiotic environmental factors, such as temperature and soil moisture, has not been fully explored. In our study, we examined plant-soil feedback responses of both cool- and warm-season native and non-native grasses to elevated temperatures (ambient and +5° C) and soil moisture (100% and 75% field capacity). In a previous experiment, grasses were grown under temperature and soil moisture conditions similar to our current study. The resultant trained soil communities served as the inoculum sources for our current experiment. We found that consistent training and experimental temperatures resulted in negative PSF, where plants produced greater biomass in soils conditioned by heterospecifics. However, the direction of PSF was reversed when training and experimental conditions were mismatched. That is, when training and experimental temperatures mirrored one another, negative PSF occurred, suggesting coexistence between the two species is likely under these conditions. However, when only training or testing temperatures were elevated, positive PSF were detected, favoring the non-native species. These alterations in plant-soil feedbacks were relatively consistent across pairings of warm- and cool-season grasses. Overall, our results indicate inconsistent year-to-year environmental conditions, such as extreme temperatures, may undermine the stabilizing forces of negative PSF and favor of non-native grasses.